Pemanfaatan Google Maps dalam Pembuatan Peta Khusus untuk Meningkatkan Ecoliteracy Peserta Didik - Sutrisno, Bambang (Jurnal Didaktika Pendidikan Dasar, 2019)
The background of this scientific writing is based on the low awareness of environmental conditions (eco-literacy) of the students, the limitations of local media and sources of learning, natural disasters, the use of ICT for negative things, and the urgency of mastering 21st-century skills. The research objectives through these Best Practices that: the students are expected to be able to make special-purpose maps and have environmental awareness (eco-literacy), able to formulate environmental problems and solutions to overcome these problems and the students have 21st-century skills. This scientific paper is in the form of Best Practice, which refers to Export Facto research because it has done by the author and obtained several results, namely: first, students are able to make a special map regarding the distribution of oil palm plantation and tin mining in the East Belitung Regency by utilizing digital map technology (google maps). Second, the students have eco-literacy. Third, the students are able to formulate solutions that can be done to deal with environmental problems in their area. Fourth, the students are trained to have 21st-century skills.